O20 Quick, simple and just as effective—comparing pm: L3 ratio to NELA, P-POSSUM and NSQIP scores in assessing mortality risk for emergency laparotomy. (30th July 2021) - Ming, J Y; Holmes, M; Pockney, P; Gani, J
Abstract: Introduction: Multiple tools (NELA, P-POSSUM, ACS-NSQIP) are available to assess mortality risks in patients requiring emergency laparotomy(1–3), but they are time-consuming to perform and have had limited uptake in routine clinical practice in many countries(4). Simpler measures, including psoas muscle: L3 vertebrae (PM: L3) ratio(5, 6), may be useful alternates. This measure is quick to perform, requiring no special skills or equipment apart from basic CT viewing software. Method: We performed an analysis on all patients in the Hunter Emergency Laparotomy Audit (HELA) database, from January 2016 to December 2017. HELA is a retrospective review of all emergency laparotomy undertaken in a discrete area in NSW, Australia. Patients with an available CT abdomen were included (N = 500/562). A single slice axial CT image at the L3 endplate level was analysed using ImageJ® software to measure the area of L3 and bilateral psoas muscles. This can be done using normal PACS software in routine practice. Result: PM: L3 ratios in this cohort have a mean of 1.082 (95%CI 1.042–1.122; range 0.141–3.934). PM: L3 ratio is significantly lower ( P < 0.00001) in those patients who did not survive beyond 30 days (mean 0.865 [95% CI 0.746–0.984]) and 90 days (mean 0.888 [95%CI 0.768–1.008]) compared to patients that survived these periods (30 day mean 1.106 [95% vs. 1.033–1.179], 90 day mean 1.112 [95% CI 1.070–1.154]). These associations are similar to those calculated by established risk assessment models. Conclusion: PM: L3 ratio is a reliable, quick and easy risk assessment tool to identify high risk patients undergoing emergency laparotomy. Take-home Message: PM: L3 ratio is a reliable, quick and easy risk assessment tool to identify high risk patients undergoing emergency laparotomy. It is comparable to NELA, P-POSSUM and ACS-NSQIP.